2004
DOI: 10.1111/j.1440-1819.2004.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of schizophrenia among national health insurance enrollees in Taiwan, 1996–2001

Abstract: As many as 96% of all residents of Taiwan have been enrolled in the National Health Insurance (NHI) program since 1996. The NHI database was used to examine the prevalence and incidence of schizoprenia. The National Health Research Institute provided a database of 200 432 random subjects, about 1% of the population, for study. By means of exclusion criteria, a random sample of 136 045 subjects as a fixed cohort dated from 1996-2001 was obtained. Those study subjects who had at least one service claim during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 20 publications
(28 reference statements)
1
50
1
Order By: Relevance
“…There are many advantages in using insurance data when studying health care utilization and expenditure for persons with diabetes comorbid with anxiety disorder, including a large number of subjects for sampling, less time and money required for psychiatric assessments, and longitudinal data to detect the incidence and risk factors [38]. However, this study has some limitations.…”
Section: Discussionmentioning
confidence: 93%
“…There are many advantages in using insurance data when studying health care utilization and expenditure for persons with diabetes comorbid with anxiety disorder, including a large number of subjects for sampling, less time and money required for psychiatric assessments, and longitudinal data to detect the incidence and risk factors [38]. However, this study has some limitations.…”
Section: Discussionmentioning
confidence: 93%
“…There are many advantages to using insurance data when studying healthcare utilization and expenditure for diabetic patients with mental illnesses, including a large number of subjects for sampling, saving time and money required to perform psychiatric assessments, and longitudinal data to detect the incidence and risk factors [42]. However, some limitations remain.…”
Section: Discussionmentioning
confidence: 97%
“…The distribution of rates in this review was asymmetric and interpreted as a possible variation in the incidence of schizophrenia. Finally, while some recent studies have suggested that the incidence rates of schizophrenia across time are in decline (Chien et al 2004;Nicole et al 1992;Suvisaari et al 1999;Takei et al 1996), more recent studies in London and Canada have shown an increase in the incidence rates of schizophrenia across time (Boydell et al 2003;Bray et al 2006). …”
Section: Incidence Of Schizophreniamentioning
confidence: 94%